Investigation of a new evaluation method for economy by one-minute supramaximal-intensity running - Tanji, F. (International Journal of Sport & Health Science, 2020)
Running economy is an important aerobic energy capacity for 800-m running performance of highly trained runners. The intensity of the running speed in 800-m race exceeds that of 120% of maximal oxygen uptake (VO2max). Therefore, we hypothesized that the economy of supramaximal-intensity running (sprint economy [SE]) was strongly associated with running performance, rather than with running economy. The aim of this study was to clarify the association of the SE in highly trained runners to the performance of 800-m running. Seven male middle-distance runners with the personal best time in 800-m of 1'48?9 ± 1?0 participated in this study. They underwent 1-minute running at 120%VO2max to be measured the SE. The SE was evaluated as the sum of energy expenditure from aerobic energy, which was calculated using oxygen uptake and respiratory exchange ratio, and from anaerobic energy, which was calculated using accumulated blood lactate concentration. The SE was not significantly associated with 800-m running performance, whereas SE was significantly associated with the VO2max and speed of 120%VO2max. These results suggest that the running speed strongly depended on the subject`s aerobic capacity because the running speed was determined by VO2max.